Impacts of Foreign Direct Investment on Vietnam’s Unemployment Rate - Huong, Luong Thanh; Cam, Nguyen Mai Nhu (Archives of Business Research, 2022)
The paper aims to analyze the influence of foreign direct investment (FDI) on the unemployment rate in the context of Vietnam. In this research, secondary data was collected from the reports World Bank and World Monetary Fund (IMF), in the period from 1991 to 2019. The findings reveal that FDI, inflation, GDP, and exchange rate negatively impact the unemployment rate, whereas trade openness has a positive influence on the unemployment rate. This means that the increase in FDI attraction can reduce the unemployment rate of Vietnamese labors. As a result, some governance implications will be proposed to help enterprises attract more FDI and decline the rate of unemployment in Vietnam.